GEOSPATIAL ASSESSMENT OF DROUGHT IN MARATHWADA REGION, INDIA - Sagar KHETWANI; Ram Babu SINGH (European Journal of Geography)
The increased frequency and intensity of droughts is a challenging phenomenon for humankind, its impact on developing nations has increased significantly. Marathwada region is chronically prone to drought and has been impacted severely between the years 2012 to2016. The paper attempts to make a spatio-temporal analysis of drought events in the Marathwada region. Three drought indices, namely Rainfall Anomaly Index (RAI), Standardized Water level Index (SWI) and NDVI Anomaly Index (NAI) were used for meteorological, hydrological and agricultural drought analysis. This study is mainly based on the secondary data sources along with field-based observation. The analysis revealed that eteorological drought events are not new for the Marathwada region. The Marathwadaregion has witnessed the worst hydrological drought in the year 2015. The correlation analysis shows that meteorological drought is directly followed by hydrological drought without any lag. The NDVI Anomaly Index of the year 2015 revealed a prevalence of agricultural drought while the results of crop Yield Anomaly Index of principal crops of region validates the outcomes of NDVI Anomaly Index.